1986
DOI: 10.1111/j.1365-2222.1986.tb00759.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE antibody‐mediated shock reaction caused by topical application of chlorhexidine

Abstract: A case of an anaphylactic shock following topical application of chlorhexidine preparation is reported. Specific skin-sensitizing antibodies against chlorhexidine were demonstrated in the serum from the patient by a passive transfer test. IgE antibodies against chlorhexidine were also detected hy radioallergosorbent technique (RAST). Paper discs conjugated with chlorhexidine-HSA (human serum albumin) significantly bound the IgE antibodies. Furthermore, all of the sera from seven other patients with shock react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 10 publications
1
48
0
2
Order By: Relevance
“…Allergic IgE antibody-mediated sensitivity to the drug can be demonstrated by positive skin tests and tests for specific serum IgE antibodies. Following the development in Japan in 1986 of a specific immunoassay for detecting chlorhexidine-reactive IgE by linking a chlorhexidine-albumin conjugate to paper discs and demonstration of specificity by inhibition with chlorguanide and the parent drug [68], experiments to identify allergenic determinants were subsequently undertaken using chlorhexidine linked to a bis-oxirane-activated solid phase [69]. To identify the fine structural features of the determinant(s) complementary to chlorhexidine-reactive IgE antibodies, a number of analogs were selected for examination.…”
Section: Chlorhexidinementioning
confidence: 99%
“…Allergic IgE antibody-mediated sensitivity to the drug can be demonstrated by positive skin tests and tests for specific serum IgE antibodies. Following the development in Japan in 1986 of a specific immunoassay for detecting chlorhexidine-reactive IgE by linking a chlorhexidine-albumin conjugate to paper discs and demonstration of specificity by inhibition with chlorguanide and the parent drug [68], experiments to identify allergenic determinants were subsequently undertaken using chlorhexidine linked to a bis-oxirane-activated solid phase [69]. To identify the fine structural features of the determinant(s) complementary to chlorhexidine-reactive IgE antibodies, a number of analogs were selected for examination.…”
Section: Chlorhexidinementioning
confidence: 99%
“…Therefore, the final concentration was 48-80 times weaker than the 0.12-0.2% product. In Japan, chlorhexidine use for sterilization of the oral cavity, hands, and catheters resulted in more than 10 cases of anaphylactic shock in the 1980s (21,22). Stephens et al (23) reported that chlorhexidine allergy has been described mainly in Japanese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Studies with radiolabeled chlorhexidine mouthrinse have shown its ability to penetrate the intact mucosal barrier of the oral cavity or intestinal tract. 33,34 Ohtoshi et al 35 reported more than 30 cases of anaphylactic shock after the topical application of chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%